PROSPECT THE STUDY OF LOCAL LEGAL AUTONOMY IN REGIONAL AUTONOMY LEGAL POLITICS - Ilyas, Ilyas; Roba, Sahra (International Journal of Business, Law, and Education, 2023)
This research examines local legal autonomy's prospects in regional autonomy's legal politics with historical, juridical normative-empirical, experimental, and comparative study methods. As a result, legal autonomy can become a new social movement and counter-cultural movement for autonomous regions or local legal community units in Indonesia to realize local wisdom and customary law autonomy in regional autonomy. “Legal autonomy is the 'new antithesis' to legal centralism, Legal Pluralism, and multiculturalism at the global, regional, national, and local levels.